1998
DOI: 10.1080/00016489850182350
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Analysis of Snoring and the Site of Airway Obstruction in Sleep Related Respiratory Disorders

Abstract: Acoustic analysis of snoring and the site of airway obstruction in sleep related respiratory disorders. Acta Otolaryngol (Stockh) 1998; Suppl 537: 47 -51.Seventy-five adult patients with sleep related respiratory disorders were examined by polysomnography with simultaneous recordings of the intraluminal pressure of the upper airway and snoring sound. Obstructed sites in the upper airway during sleep were determined by comparing the amplitude of respiratory fluctuation of the pressures in the epipharynx, mesoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
2
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 1 publication
2
43
2
2
Order By: Relevance
“…17,19 The PF of snores generated from soft palate, tonsils, epiglottis, and base of tongue may lie in the range of 105-189, 85-201, 331-510, and 1215-1277 Hz, respectively 3 ; the fundamental frequency of palatal snores and tongue base snores may be of 103 ± 35 and 332 ± 145 Hz, respectively. 33 The proposed markers (PF1 and PSF), which signify approximated modes with highest coupling strength, have clearly demonstrated their capability to discriminate between snorers with and without OSA (p < 0.0001). To further appraise the markers, we comparatively evaluated their diagnostic performance with those obtained from conventional power spectral analysis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…17,19 The PF of snores generated from soft palate, tonsils, epiglottis, and base of tongue may lie in the range of 105-189, 85-201, 331-510, and 1215-1277 Hz, respectively 3 ; the fundamental frequency of palatal snores and tongue base snores may be of 103 ± 35 and 332 ± 145 Hz, respectively. 33 The proposed markers (PF1 and PSF), which signify approximated modes with highest coupling strength, have clearly demonstrated their capability to discriminate between snorers with and without OSA (p < 0.0001). To further appraise the markers, we comparatively evaluated their diagnostic performance with those obtained from conventional power spectral analysis.…”
Section: Discussionmentioning
confidence: 89%
“…To further appraise the markers, we comparatively evaluated their diagnostic performance with those obtained from conventional power spectral analysis. PF, a typical indicator for identifying apneic and benign snorers, 17,19 as well as locating snoring sites, 3,33 was estimated from the Welch's method 48 using a 256-sample (%23 ms, an assumption of quasistationary period similar to that of speech signals 9 ) and a 512-sample (%46 ms, identical to the present experimental condition) Hanning window with 75% overlap. Results confirm that the proposed markers could yield better diagnostic accuracy than the conventional PF indicator in detecting OSA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Saunders et al [4] identified that palatal snorers produced sound with a centre frequency below 90 Hz, whereas all pure tongue-base snorers produced sound with a centre frequency above this value, thereby allowing one to differentiate between the two snoring causes and decide on a more appropriate treatment strategy in each instance. Further investigations have concurred with this idea and claimed that it should indeed be possible to use sound spectral analysis to determine anatomically obstructive areas [5][6][7]. Previously, a 'multidimensional voice program' (MDVP) has been used for acoustic analysis.…”
Section: Introductionmentioning
confidence: 89%
“…While Miyazaki et al [55] identified only seven cases of increased nasal resistance in a group of 54 patients with OSA (13%), other cases have been reported in which surgical procedures on the nose by themselves relieved mild OSA [70,76]. A review of the literature yielded nine publications reporting the success of surgical procedures on the nose in patients with OSA, which include patients' pre-and postoperative sleep laboratory findings.…”
Section: Surgical Therapymentioning
confidence: 97%